Struktury organizacyjne projektów we współczesnych organizacjach - Krzos, Grzegorz; Klonowski, Przemysław (The Structures of Projects in Modern Organizations, 2008)
The article contains an attempt of analysis and verification of organizational Solutions suggested by PMI in the context of a project manager's work in investigated companies and local government units. The PMI methodology specifies six solutions of project's location and an organization in project management in respect of an organization's structure. Among them are: 1. Functional structure. 2. Functional and coordination structure. 3. Week matrices (matrix) structure. 4. Balanced matrix structure. 5. Strong matrix structure. 6. Clean project structure. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 102-111